Actors of international cooperation in prewar Japan: the discourse on international migration and the League of Nations Association of Japan - Terada, Kuniyuki (Japan in Ostasien, 2018)
The book is the first study on the history of one of the most powerful semi-governmental international organizations in interwar Japan: the League of Nations Association of Japan. Established in 1920 for the purpose of achieving the spirit of the League of Nations, the association was at the center of Japanese international cooperation and, even after Japan’s withdrawal from the League itself, acted vigorously as a member of the non-governmental International Federation of League of Nations Societies.Based on extensive multi-archival research, this book explores how members of the association including both governmental and non-governmental actors tried to address international problems such as racial equality, migration, labour, and population. By doing so, the book reconstructs a little-known history of Japan’s international cooperation and puts it into the context of global history.
Keywords: Kokusai Renmei Kyōkai (Japan); Japan -- Foreign relations -- 1912-1945; Japan -- Politics and government -- 1912-1945; Hochschulschrift; Geschichte 1894-1939; Internationale Kooperation; Internationale Politik; Japan; Geschichte 1920-1927; Kokusai Renmei Kyōkai